KONSEP DIRI BERKORELASI DENGAN BODY IMAGE PADA PASIEN OPEN REDUCTION INTERNAL FIXATION (ORIF) - Roma Sitio; Khalimatun Sa’ziah Putri (Journal Keperawatan, 2023)
A fracture is a break in the continuity of the bone, bone tissue, or cartilage which is generally caused by force. The operative treatment in fracture cases is Open Reduction Internal Fixation (ORIF). Patients after ORIF installation often have psychological problems. One of them is self-concept, namely body image, self-identity, self-ideal, and self-esteem. The purpose of this study was to determine the relationship between self-concept and body image in ORIF patients at Meuraxa Hospital Banda Aceh, the relationship between self-esteem and body image in ORIF patients, the relationship between self-identity and body image in ORIF patients, the relationship between self-role and body image in ORIF patients. This study uses the Chi-Square correlation method with = 0.05. The results of this study showed that P-value = 0.000 <0.05 so the Ho hypothesis was rejected, meaning that there was a significant relationship between self-concept and body image in ORIF patients at Meuraxa Hospital Banda Aceh.